DETERMINATION OF STOPPING POINT LENGTH DEPENDING ON TRAFFIC INTERVALS OF PUBLIC TRANSPORT - T. N. Samoilovich (Наука и техника)
The paper considers a probability of simultaneous arrival more than one route vehicle at a stopping point  depending on a traffic interval.  Probability dependences of arrival more than one route vehicle on a traffic interval have been determined in the paper. The paper proposes calculated lengths of route vehicles, a methodology for calculation of stopping point length. A calculation example is given in the paper.